Case study: Suki group of restaurants–transformation recipe - Wee, Chow-Hou (2022)
This case study overviews the successful growth of the Suki Group of restaurants in Singapore. Blending Asian and Western cuisines and offering a value for money experience, the Suki Group has expanded from a single restaurant in 2002 to a major chain employing over 1100 people across 31 outlets in Singapore. As a case study for students and managers it highlights the importance of value creation, customer and employee focus, sound leadership and a capacity for innovation.